Fostering Academic Excellence in Higher Education: A SEM Analysis of Total Quality Management, Organizational Innovation, and Institutional Performance in the UAE - Alhosani, Ahmed Ibrahim; Yaakub, Kamarul Bahari (European Journal of Social Science Education and Research, 2025)
Higher Education Institutions (HEIs) in the United Arab Emirates (UAE) face intense pressure to evolve from teaching-centric bodies into innovation-driven engines of economic growth. This study develops and tests a structural model to investigate the mechanisms through which quality management translates into superior institutional outcomes. Specifically, it examines the mediating role of organizational innovation in the relationship between Total Quality Management (TQM) practices and institutional performance. A quantitative, cross-sectional survey was conducted, gathering data from 342 academic staff at major public and private universities in Abu Dhabi. Structural Equation Modeling (SEM) revealed that TQM has a significant positive direct effect on both organizational innovation and institutional performance. Furthermore, organizational innovation demonstrated a strong positive impact on institutional performance. Bootstrapping analysis confirmed that organizational innovation acts as a significant partial mediator, clarifying that a substantial portion of TQM's benefit is channeled through the enhancement of innovative capabilities. The findings provide an empirically validated framework for university leaders, suggesting that TQM is a foundational strategy whose value is maximized when it is leveraged to cultivate a culture of pedagogical and administrative innovation, thereby driving sustainable institutional excellence.
Keywords: Total Quality Management (TQM), Organizational Innovation, Institutional Performance, Higher Education, UAE, Structural Equation Modeling (SEM)